METHODS AND MEANS OF IMPROVING RESOURCE OF THE TRIBOCOUPLING - Makarenko, M. H. (Science and Transport Progress, 2008)
The opportunity of increasing the resource of parts of tribosystems of machines and mechanisms by the method of wear autocompensation with the use of external energy source for formation and transfer of recovering material to the contact zone is considered.